2021
DOI: 10.3390/en14237900
|View full text |Cite
|
Sign up to set email alerts
|

Will Aggregator Reduce Renewable Power Surpluses? A System Dynamics Approach for the Latvia Case Study

Abstract: Power demand-side management has been identified as one of the possible elements towards a more flexible power system in case of increased capacities of variable renewable energy sources—solar and wind energy. The market coordinators or aggregators are introduced to adjust the electricity consumption by following the market situation. However, the role of aggregators is mainly analysed from the economic perspective, and the demand side management is performed to maximise the utilisation of low price power duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In general, the process of developing a system dynamics model consists of several sequential steps. These steps include problem formulation, which is the identification of dynamic hypotheses that explain the causes of the problem, model formulation and simulation, which means model testing to assess its correspondence to the real situation, as well as policy formulation and drawing conclusions [15,27].…”
Section: The Structure Of the Exploratory Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, the process of developing a system dynamics model consists of several sequential steps. These steps include problem formulation, which is the identification of dynamic hypotheses that explain the causes of the problem, model formulation and simulation, which means model testing to assess its correspondence to the real situation, as well as policy formulation and drawing conclusions [15,27].…”
Section: The Structure Of the Exploratory Modelmentioning
confidence: 99%
“…The values for these elements are defined through mathematical equations and constants. In the hourly model of the dynamic system, the household consumption profile is assumed based on input data obtained from a system dynamics model developed in 2021 for studying the potential of aggregators to reduce renewable energy surplus in Latvia [27]. The model assumes hourly electricity prices based on historical indicators from the 2021 NordPool electricity market [21], considering them as indicative of electricity price trends for the next decade.…”
Section: Model Components and Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature about aggregators is extensive and covers a broad area, from describing the value of aggregators for the electricity system [10,11] and consumers [12], to aggregator profit maximization through optimal scheduling [13,14], to aggregator behavior in the electricity markets [15][16][17][18][19][20][21]. The literature on DR and aggregator participation in electricity markets has shown that DR can be an effective tool for balancing supply and demand on the grid and that aggregators can play an important role in providing flexibility and balancing services [22][23][24][25][26].…”
Section: Literature Review Of Types Of Markets In Which Aggregators C...mentioning
confidence: 99%
“…Considering this framework, it is now evident that, among various types of energy companies, the right choice could be an Aggregator in accordance with the expertise gained operating local facilities, infrastructures, and services connected to DER production. The Aggregator has, in fact, the role of gathering electricity demand, the energy produced, and load flexibility from the prosumer's devices, engaging different electricity markets in which electricity and ancillary services are traded [27]. The literature on Aggregators is not so extensive, but the most acknowledged setup for this entity is the local flexible market operator, which supervises the cluster's activities and internal transactions, as described in [28].…”
mentioning
confidence: 99%